Irritation Design: Updating Steering Theory in the Age of Governance - Mölders, Marc (Politics and governance, 2021)
Is steering still a viable concept? The article answers this question with a conditional yes. On the one hand, its conceptual core remains intact. Getting others—who are considered to be idiosyncratic—to solve rather than pose societal problems is no less relevant for recent governance analyses. On the other, steering as a concept needs some updates in terms of subjects, objects, and ways of steering. Beyond merely extending the list of possible subjects and objects of steering, the concept of irritation design is proposed. It stresses that making communication hard to ignore can be a matter of design. Modern society seems to be crowded with steering entities, many of which displaying smart irritation designs. This leads to complex constellations. Yet it remains valuable to analyze strategies of influence because despite all dynamics and happenstance, different chances of impact correlate with different irritation design. Still, we have to account for two aspects: 1) Capacities (beyond money or power) needed for designing irritations are unequally distributed; 2) material effects and empirical boundaries have their share in a decreased ignorability.